Analytical expressions for transient diffusion layer thicknesses at non uniformly accessible electrodes - Molina, A; Gonzalez, J; Henstridge, M; Compton, R (2011)
Explicit analytical expressions for the diffusion layer thicknesses of disk and band electrodes of any size, under transient conditions have been deduced. We have applied these expressions to constant potential chronoamperometry and Linear Sweep Voltammetry (LSV). The analysis of the diffusion layer thickness and concentration profiles of electroactive species corresponding to the application of a constant potential have allowed us to characterise the evolution of the mass transport from linear (high sizes) to radial (microelectrodes). The influence of the time pulse, scan rate and the electrode radius has been analyzed, with limiting expressions corresponding to E E 0 and E E0 were also deduced. The conditions required to attain a stationary state are discussed. © 2011 Elsevier Ltd. All rights reserved.